I knew I loved you before I met you An exploratory study on romantic relationships built through texting. - Futol, Adora Faye T.; Geonzon, Hazeline A. (Adora Faye T. Futol and Hazeline A. Geonzon, 2009)
This paper is entitled "I Knew I Love You Before I Met You: An Exploratory Study on Romantic Relationships Built Through Texting." This study aims to determine whether this kind of a relationship follows the patterns of conventional relationship development, to identify the most common problems that arise in this kind of relationship, and the quality and stability of romantic relationships built through texting. This study was conducted in Tacloban City. The researchers used purposive sampling in choosing the research respondents in which certain criteria have to be met for the purpose of having an in-depth treatment of the study. The samples of the study consisted of 14 individuals, seven males and seven females. These individuals have agreed to be romantically involved even without seeing or meeting their partners in person yet. In the analysis of the data gathered, the researchers came up with common themes taken from the interview of the respondents. The results of the study indicated that: Romantic relationships built through texting follow the same pattern of relationship development of those that started out the conventional way. It has also been found out that the common problems that the couples in this kind of relationship do not qualitatively differ from those that couples in conventional relationships go through. Finally, trust and commitment can also be established in romantic relationships built through texting.